The effects of an 8-week knitting program on osteoarthritis symptoms in elderly women: A pilot randomized controlled trial - Leonard, Guillaume; Paquet, Nicole; Guitard, Paulette; Toupin-April, Karine; Cavallo, Sabrina; Paterson, Gail; Aydin, Sibel Z; Bakirci, Sibel; Coulombe-Lévêque, Alexia; Brosseau, Lucie (Université d'Ottawa | University of Ottawa, 2021)
Exercise therapy is effective in reducing symptoms and disability associated with hand osteoarthritis (HOA) but often has low adherence. An intervention consisting in a meaningful occupation, such as knitting, may improve adherence to treatment. This pilot randomized controlled trial (RCT) studied the adherence and clinical effectiveness of a knitting program in older females suffering from HOA to evaluate the acceptability of this intervention and assess the feasibility of a larger-scale RCT.
Keywords: Exercise; Hand; Knitting; Osteoarthritis; Pain; Stiffness; Women; Aged; Exercise Therapy; Female; Hand; Humans; Pilot Projects; Quality of Life; Osteoarthritis